MISLEADING DIGITAL ADVERTISING: ITS ROLE IN INFLUENCING USER BEHAVIOR AND TRIGGERING CRIMINAL LIABILITY - Maaitah, Qais Khaleel; Maha, Elsaka; Alsaraireh, Naser (Veredas do Direito, 2026)
Advertising has become one of the most important methods of marketing products, Therefore, advertising has become one of the most important methods of marketing products, Therefore, the consumer has become more vulnerable to misinformation and this represents a danger to the security and safety of the consumer from misleading advertising, which has effects to attract his attention, whether by incorrect information or by the figures, shapes, colors, and presenting non-real specifications aimed at creating an unfair impression of the consumer about the goods or services. This it is due to his lack of experience and insufficient awareness, making him a victim of misleading advertisements. Therefore, legal protection is necessary to protect him from providers or advertiser from misleading advertisements. A variety of legislations have focused on protecting consumers from misleading advertisements and stipulating guidelines for commercial advertisements to ensure honesty in their advertisements and to avoid exaggerated praise in describing the product or service. Since advertisers are spending more effort to reach out to deliver goods and services in all ways and influences to reach the consumer's intention to contract.